THE ROLE OF COMMUNICATION NETWORK IN DEVELOPING THE COHESIVENESS OF DRUG PLANT FARMER GROUP IN WEST JAVA - Bakti, dkk, Iriana (EDUTECH, 2015)
Abstract, This research entitled "Communication network role in developing a cohesive groups of medicinal plant farmer in West Java"; Focusing on the existence of group of medicinal plant farmer, committed to converge with other communities through interaction and collaboration in order to establish a communication network on medicinal plant farming management. Nevertheless the communication network has not yet exhibited the expected dynamic of the group. The activities occur are still limited to meeting among farmer's groups in disseminating a particular program and as a social function. The aims of this research are to explore (1) levels of communication network in dissemination of medicinal plants information. (2) The level of cohesiveness of groups involved in communication network. Method used in this research is descriptive, describing problems with qualitative and quantitative data to perceive deeper understanding. Results show that (1) Level of communication network among member of the group or with other groups is categorically high, as they frequently discuss, creates dialogue, and received information on medicinal plants problems. (2) Level of cohesiveness is also high, as most members of the farmer's group have same perception towards medicinal plants, enthusiasm in joining group's activities, willing to be given any task, and enjoying the cooperation among members of the groups or with other groups. Keywords : Communication Network, Cohesiveness, Medicinal Plant Abstrak, Penelitian ini berjudul "Peran  jejaring komunikasi   dalam membangun kohesivitas kelompok tani tanaman obat di Jawa Barat". Penelitian ini merujuk pada keberadaan kelompok tani tanaman obat yang memiliki komitmen  untuk berjumpa dengan sesama komunitas lainnya melalui interaksi dan berkolaborasi sehingga terbangun jaringan komunikasi dalam pengelolaan tanam obat, namun jaringan komunikasi kurang menunjukkan  kedinamisan kelompok, aktivitasnya lebih mengarah kepada sekedar upaya pertemuan kelompok tani untuk menjelaskan informasi tentang suatu program dan tempat menjalin tali silaturahmi. Tujuan Penelitian adalah untuk mengetahui 1) Tingkat jejaring komunikasi dalam penyebarluasan informasi tanaman herbal. 2) Kohesivitas kelompok yang terlibat dalam jejaring komunikasi. Metode yang digunakan dalam penelitian ini adalah metode deskriptif yang menggambarkan masalah berdasarkan sifat data kuantitatif dan kualitatif, sehingga dapat diperoleh pemahaman yang lebih mendalam tentang masalah yang diteliti. Hasil Penelitian menunjukkan bahwa: 1) Anggota kelompok tani sering membicarakan, berdialog, dan menerima masukan  tentang masalah tanaman obat dengan sesama anggota kelompok maupun dengan pihak lain, sehingga tingkat jejaring komunikasi dalam kelompok ini dikategorikan tinggi. 2) Sebagian besar anggota kelompok tani memiliki kesamaan pandangan tentang tanaman obat, senang mengikuti kegiatan kelompok, senang diberi tugas, dan sering bekerja sama baik dengan sesama anggota kelompok maupun dengan pihak lain. Dengan demikian, tingkat kohesivitas kelompok tani tanaman obat dikategorikan tinggi. Kata kunci: Jejaring komunikasi,  Kohesivitas. (ditambahan minimal 1 Kata kunci lagi)